The influence of thread geometry on biomechanical load transfer to bone: A finite element analysis comparing two implant thread designs - Manisha G Herekar; Viraj N Patil; Shahnawaz S Mulani; Megha Sethi; Omkar Padhye (Dental Research Journal, 2014)
Background: The success of dental implants depends on the manner in which stresses are transferred to the surrounding bone. An important consideration is to design an implant with a geometry that will minimize the peak bone stresses caused by standard loading. The aim of this study was to assess the influence of implant thread geometry on biomechanical load transfer and to compare the difference between two different thread designs. Materials and Methods: A three-dimensional finite element model of D2 bone representing mandibular premolar region was constructed. Two implants of differing thread geometries, 13-mm length, and 4-mm diameter along with superstructures were simulated. One design featured fourfold microthread of 0.4-mm pitch, 0.25-mm depth in the crestal one-third; 0.8-mm pitch, 0.5-mm depth in the apical two-third. The other design had a single-pitch microthread of 0.8-mm pitch, 0.25-mm depth in the crestal one-third; 0.8-mm pitch, 0.5-mm depth in the apical two-third. A static axial load of 100-N was applied to the occlusal surface of the prosthesis. ANSYS CLASSIC 9.0 (PA,USA)software was used for stress analysis as von Mises stresses. Results: A comparison of von Mises stresses between two thread designs revealed that fourfold microthread allows better stress distribution within the implant body by 43.85%, abutment by 15.68%, its superstructure by 39.70% and 36.30% within cancellous bone as compared to single-pitch microthread. The effective stress transfer to the cortical bone is lowered by 60.47% with single-pitch microthread. Conclusion: Single-pitch microthread dissipates lesser stresses to cortical bone while the implant body, abutment, and superstructure absorb more stress. This will have a positive influence on the bone-implant contact and contribute to preservation of crestal bone. Implant with single pitch microthread will thus be preferable to be used in areas where the amount of cortical bone available is less.